2022
DOI: 10.3390/nano12152603
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophilic Nanotextured Surfaces for Dental Implants: Influence of Early Saliva Contamination and Wet Storage

Abstract: Hydrophilic and nanotextured surfaces for dental implants have been reported as relevant properties for early osseointegration. However, these surface characteristics are quite sensitive to oral interactions. Therefore, this pilot study aimed to investigate the superficial alterations caused on hydrophilic nanotubular surfaces after early human saliva interaction. Titanium disks were treated using an anodization protocol followed by reactive plasma application in order to achieve nanotopography and hydrophilic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Firstly, implant surfaces associated with nanostructured topography have been currently reported as a significant strategy to reduce corrosion rates and generate higher biocompatibility [ 29 ], as well as, it has demonstrated mechano-antibacterial properties generating minimized taxes of bacterial adhesion [ 30 ]. Moreover, nanostructured surfaces have been demonstrated to be easily modified in terms of wettability, Kunrath and colleagues have demonstrated the hydrophilization of nanotextured surfaces by applying Ar/O 2 reactive plasma [ 31 ] and Zhang and co-authors have shown the option of hydrophobization of nanotubular surfaces creating anti-fouling/antibacterial surfaces [ 32 ].…”
Section: Methods To Develop Bddss For Oral Bone- and Periodontal-rela...mentioning
confidence: 99%
“…Firstly, implant surfaces associated with nanostructured topography have been currently reported as a significant strategy to reduce corrosion rates and generate higher biocompatibility [ 29 ], as well as, it has demonstrated mechano-antibacterial properties generating minimized taxes of bacterial adhesion [ 30 ]. Moreover, nanostructured surfaces have been demonstrated to be easily modified in terms of wettability, Kunrath and colleagues have demonstrated the hydrophilization of nanotextured surfaces by applying Ar/O 2 reactive plasma [ 31 ] and Zhang and co-authors have shown the option of hydrophobization of nanotubular surfaces creating anti-fouling/antibacterial surfaces [ 32 ].…”
Section: Methods To Develop Bddss For Oral Bone- and Periodontal-rela...mentioning
confidence: 99%
“…For example, saliva can damage the super-hydrophilic nano-textured surface of dental implants, which may affect bone healing. 51 Furthermore, the high wetness of saliva and the presence of various proteins and mucins prevent the strong and stable adhesion of drugs and biomaterials to the oral mucosa and dentoidin. 52 Besides saliva, the wet environment caused by fluid from food and drink intake hampers the retention of polymeric materials at the lesion site.…”
Section: Highly Movable and Wet Environmentmentioning
confidence: 99%
“…On the other hand, surface treatments applying subtractive methods such as etching, blasting, and anodizing, promote surface properties with higher corrosion resistance compared to additive-coated surfaces, suggesting lower rates of particle release during the biocorrosion process. [ 40 , 41 ] Results by Schwarz et al [ 42 ] revealed that implantoplasty on modified surfaces by using diamond burs promoted the release of Ti particles from all tested samples, which might be linked to inflammation. Thus, techniques using less aggressive approaches, e.g., with non-metallic instruments, to treat dental implant surfaces affected by peri-implantitis might reduce the possibility of Ti particles release.…”
Section: Effect Of Titanium Particles and Ions On The Cellular Respon...mentioning
confidence: 99%